An empirical study of trade effect on culture - Jing Yan; Ning Li; Feng Yu (Journal of Applied Economics, 2024)
Given the global dominance of American movies, they play a significant role in presenting U.S. ideology and culture to the world, thus raising concern of undermining domestic culture. This paper investigates whether trade shapes culture by studying the impact of imported American movies on Chinese cultural values measured by Hofstede Index. The results show that demand for American movies has a positive and statistically significant effect on individualism, power distance, long-term orientation and indulgence. While many studies show evidence that cultural similarity stimulates trade, there is almost no empirical evidence on how international trade affects culture. This study contributes to the literatures related to the relationship between culture and trade by filling this void. The findings of this study also have strong policy implications by bringing empirical evidence to the debate on free trade of cultural products.
Keywords: 330; culture; International trade; movie industry